A pretreatment method for grinding wastewater

By adopting a combination of multiple combined sedimentation and specific flocculants in the pretreatment stage of the grinding wastewater, the problem of low removal efficiency of nano-sized suspended particles is solved, efficient removal and concentration is achieved, and treatment costs and pollution risks are reduced.

CN118812089BActive Publication Date: 2025-03-14DONGGUAN SANRENXING ENVIRONMENTAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411129742.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2025-03-14
Estimated Expiration
2044-08-16

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove nano-scale solid suspended particles in grinding wastewater, resulting in a reduced treatment efficiency of sewage treatment plants and an increase in daily operation and maintenance costs.

Method used

The removal efficiency of nano-sized suspended particles is improved by adjusting pH, deemulsifying, filter layer design and multi-layer filtration technology.

Benefits of technology

It significantly improves the removal efficiency of solid suspended matter in grinding wastewater, reduces the concentration and turbidity of suspended matter in wastewater, and reduces the risk of blocking and maintenance costs of subsequent treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004997464680000091
    Figure BDA0004997464680000091
  • Figure BDA0004997464680000101
    Figure BDA0004997464680000101
Patent Text Reader

Abstract

The present invention relates to the field of wastewater treatment, and specifically discloses a pretreatment method for grinding wastewater. The pretreatment method for grinding wastewater comprises the following steps: S1, taking grinding wastewater, adjusting the pH to 7 with sodium hydroxide or sulfuric acid; S2, adding a demulsifier to the grinding wastewater, stirring, filtering, and taking the filtrate; S3, adding ferroferric oxide magnetic nanoparticles and an adsorbent to the filtrate, stirring, precipitating, and taking the upper solution; S4, adding aluminum sulfate and cationic polyacrylamide for sludge dehydration to the upper solution, stirring, and precipitating; S5, passing the filtrate through a cotton filter layer and a ceramic nanofiltration membrane layer in sequence, and obtaining the pretreated grinding wastewater. The pretreatment method of the present invention can efficiently remove suspended solids in grinding wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of wastewater treatment, in particular to a pretreatment method for grinding wastewater. Background Art

[0002] The grinding wastewater in the new display device industry chain mainly comes from the production wastewater discharged during the production of electronic glass devices such as flat panels and computer screens. The grinding wastewater contains a large amount of nano-particles, metal oxides and organic matter. The overall pollutant concentration is not high and the biodegradability is poor. If it enters the sewage treatment plant directly without special treatment, it will greatly reduce the treatment efficiency of the sewage treatment plant.

[0003] At present, for the treatment of grinding wastewater, processes are usually added to the physical precipitation filtration to specifically remove special suspended solids, such as physical sedimentation, chemical coagulation, flotation, and coagulation. The suspended solids contained in the grinding wastewater of the new display device industry chain are mostly nanometer-sized. The above conventional treatment processes are mostly targeted at micron-sized particles, and it is difficult to remove nanometer-sized particles with smaller particle sizes. Therefore, membrane filtration is an effective way to remove nanometer-sized suspended particles. However, due to the large amount of grinding wastewater and the high content of nanometer-sized particles, the filter membrane is easily blocked during the filtration process. High-frequency backwashing is required to restore the normal filtration function of the filter membrane, which easily increases the daily operation and maintenance costs. Therefore, there is still room for improvement. Summary of the invention

[0004] In order to improve the removal efficiency of nano-solid suspended particles in the pretreatment stage of grinding wastewater, the present application provides a pretreatment method for grinding wastewater.

[0005] In the first aspect, the present application provides a method for pre-treating grinding wastewater, which adopts the following technical solution:

[0006] S1, take the grinding wastewater and adjust the pH to 7 with sodium hydroxide and sulfuric acid;

[0007] S2, adding a demulsifier to the grinding wastewater, stirring, filtering, and taking a filtrate, wherein the filter layer used in the filtering process is prepared by mixing ceramic powder, activated carbon and chitosan;

[0008] S3, adding ferroferric oxide magnetic nanoparticles and an adsorbent to the filtrate, stirring, settling, and taking an upper layer of the solution, wherein the adsorbent is a mixture of activated carbon, diatomaceous earth, and magnesium oxide;

[0009] S4, adding aluminum salt flocculant and cationic polyacrylamide for sludge dehydration to the upper solution, stirring, settling, and obtaining a filtrate;

[0010] S5, passing the filtrate through a cotton filter layer and a ceramic nanofiltration membrane layer in sequence, wherein the cotton filter layer is prepared by mixing long-staple cotton, diatomaceous earth and silicate, so as to obtain pretreated grinding wastewater.

[0011] By adopting the above technical scheme, on the basis of traditional coagulation technology, multiple combined sedimentation methods are adopted, and specific aluminum salt flocculants and cationic polyacrylamide for sludge dehydration are applied to improve the removal efficiency of suspended solids in grinding wastewater.

[0012] First, adjust the pH of the grinding wastewater to 7 to prevent the wastewater from being acidic or alkaline, which will affect subsequent sedimentation. Through the action of demulsifiers, organic matter with milky properties and colloidal structure in the grinding wastewater is broken, making it easier for suspended solid particles to achieve gravity sedimentation. Through filtration, some solid particles with large particle sizes are removed. Ceramic powder provides a stable support structure and adsorption effect, activated carbon provides efficient adsorption capacity, and chitosan is used to enhance the overall adsorption and filtration effect. The mixed filter layer has a high removal efficiency for wastewater containing nano-scale solids and can effectively reduce the concentration and turbidity of suspended matter in the wastewater.

[0013] Under stirring conditions, the ferroferric oxide magnetic nanoparticles and adsorbent collide with the nano-silicon dioxide particles in the grinding wastewater to form polymers with larger particle sizes. Some of the larger polymers settle under the action of gravity. Among them, activated carbon, diatomaceous earth and magnesium oxide each play a unique role in the mixed adsorbent, forming a synergistic effect. Activated carbon provides strong adsorption capacity, diatomaceous earth enhances the physical interception effect, and magnesium oxide can promote the removal of nano solids through catalysis, further removing nano solids. The three together allow the adsorbent to work for a long time and improve the removal efficiency of nano cabinet particles.

[0014] Aluminum salt flocculant and cationic polyacrylamide for sludge dewatering are added to the upper solution. The high molecular weight cationic polyacrylamide for sludge dewatering has better precipitation and flocculation effect. In the process of synergistic precipitation of cationic polyacrylamide for sludge dewatering and aluminum salt flocculant, the amino group therein can react with aluminum ions to form a complex, and combine with the suspended polymer in the upper solution to form a larger floc agglomerate, and further gravity sediment the polymer in the upper solution in a suspended state; in addition, the reaction process of aluminum salt flocculant and cationic polyacrylamide for sludge dewatering synergistically forming a complex further accelerates the formation of flocs, improves the flocculation and sedimentation speed, and solves the problem of slow flocculation speed of high molecular weight cationic polyacrylamide for sludge dewatering during the flocculation process.

[0015] Finally, the filtrate is passed through the cotton filter layer and the ceramic nanofiltration membrane layer in turn to further remove nano solids with smaller particle sizes. The mixed cotton filter layer combines the fiber structure of long-staple cotton, the adsorption of diatomaceous earth and the stability of silicate to form an efficient filtration barrier that can more effectively intercept and remove nano solid particles with smaller particle sizes in wastewater, thereby improving the overall removal efficiency.

[0016] Preferably, in step S2, the weight ratio of the ceramic powder, the activated carbon and the chitosan is (5-6):(2-3):3.

[0017] By adopting the above technical solution, a tightly structured filtration layer is formed, which effectively removes solid particles with a large particle size, further purifies the grinding wastewater, and is beneficial to the next step of treatment of the grinding wastewater.

[0018] Preferably, in step S3, the weight ratio of the activated carbon, the diatomaceous earth and the magnesium oxide is (5-8): (3-4): 0.5.

[0019] By adopting the above technical solution, the dosage of activated carbon, diatomaceous earth and magnesium oxide is optimized, the adsorption efficiency of the adsorbent is improved, and the nano solid particles in the wastewater are further reduced.

[0020] Preferably, the weight ratio of the long-staple cotton, the diatomaceous earth and the silicate is (5-8):(4-7):3.

[0021] By adopting the above technical solution, the dosage of long-staple cotton, diatomaceous earth and silicate is optimized, so that the structure of the cotton filter layer is tighter, with good filtering and absorption effect, effectively intercepting nanoparticles with small average particle size, and improving the removal efficiency of nano solid particles.

[0022] Preferably, the mass concentration of the ferroferric oxide magnetic nanoparticles in the filtrate is 1-2 g / L and the mass concentration of the adsorbent in the filtrate is 30 / 50 g / L.

[0023] By adopting the above technical scheme, grinding wastewater and ferroferric oxide magnetic nanoparticles in a specific mass ratio are agglomerated and precipitated, which is beneficial to maximizing the sedimentation degree of suspended solids in the grinding wastewater; at the same time, it is not easy to add excessive ferroferric oxide magnetic nanoparticles and increase the processing pressure of the subsequent filter membrane.

[0024] Preferably, the mass concentrations of the aluminum salt flocculant and the cationic polyacrylamide for sludge dehydration in the upper solution are 0.5-1 g / L and 1-2 g / L, respectively.

[0025] By adopting the above technical scheme, according to the concentration of suspended matter in the upper solution, flocculants are added in a specific proportion, and cationic polyacrylamide is used for sludge dehydration to carry out flocculation and precipitation, which can improve the flocculation and sedimentation effect with the minimum dosage and prevent excessive addition of admixtures from causing additional pollution to the water.

[0026] Preferably, the aluminum salt flocculant is composed of aluminum chloride and aluminum sulfate in a weight ratio of 1:(2-3).

[0027] By adopting the above technical solution, using the above specific ratio of ferrous sulfate and ferric chloride as demulsifiers, the stable double electric layer structure and emulsification system can be destroyed, and the organic matter with emulsion characteristics and colloidal structure in the grinding wastewater can be effectively broken, making it easier for the suspended solid particles to achieve gravity sedimentation. At the same time, it is also beneficial to further enhance the polymerization efficiency of ferroferric oxide magnetic nanoparticles and suspended matter in the grinding wastewater, and further improve the sedimentation efficiency.

[0028] Preferably, the demulsifier is composed of ferrous sulfate and ferric chloride in a weight ratio of (4-5):1.

[0029] By adopting the above technical scheme, by adopting the above technical scheme, using aluminum chloride and aluminum sulfate in a specific proportion as flocculants, the charge on the surface of solid suspended matter in the grinding wastewater can be neutralized, the charge repulsion between suspended particles can be reduced, and floccules can be formed with the solid suspended matter at the same time to achieve a better gravity sedimentation effect. The synergy of the two is conducive to further improving the efficiency of flocculation sedimentation.

[0030] Preferably, in step S5, the ratio of the thickness of the cotton filter layer to the thickness of the ceramic nanofiltration membrane layer is (30-50):3.

[0031] By adopting the above technical solution, the thickness of the cotton filter layer and the ceramic nanofiltration membrane layer is optimized, and the interception of solid particles with small particle size is further improved, so as to improve the purity of the final product and reduce its turbidity.

[0032] Preferably, the stirring speed of S3 is 200-300 r / min, and the stirring time is 10-15 minutes.

[0033] By adopting the above technical solution, a faster stirring speed and a shorter stirring time are used in S3, so that the ferroferric oxide magnetic nanoparticles can fully contact with the solid suspended particles in the grinding wastewater in a short time to form a large number of agglomerates.

[0034] Preferably, the stirring speed of S4 is 50-100 r / min, and the stirring time is 20-30 minutes.

[0035] By adopting the above technical solution, a slower stirring speed and a longer stirring time are used in S4, so that the flocs can be fully contacted with the agglomerates generated in step S3, thereby improving the sedimentation efficiency of the agglomerates; at the same time, the low stirring speed is not easy to destroy the morphology of the flocs, causing floc breakage and affecting the sedimentation efficiency.

[0036] In summary, this application has the following beneficial effects:

[0037] 1. Based on the traditional coagulation technology, multiple filtration methods are adopted, and specific aluminum salt flocculants and cationic polyacrylamide for sludge dehydration are applied to improve the removal efficiency of suspended solids in grinding wastewater. Firstly, the pH value of the grinding wastewater is adjusted to 7, and under stirring conditions, a demulsifier is used to improve its filtration efficiency, and most of the particles with larger nano-particle size are removed only through a specific filter layer, and then the magnetic nano-particles of ferroferric oxide and the adsorbent collide with the nano-silicon dioxide particles in the grinding wastewater to form polymers with larger particle size and settle under the action of gravity; aluminum salt flocculants and cationic polyacrylamide for sludge dehydration are added to the upper solution for synergistic flocculation, and the polymers in the upper solution in a suspended state are further subjected to gravity sedimentation; in addition, the reaction process in which the aluminum salt flocculants and cationic polyacrylamide for sludge dehydration synergistically form a complex further accelerates the formation of flocs, increases the speed of flocculation and sedimentation, and solves the problem of slow flocculation speed of high molecular weight cationic polyacrylamide for sludge dehydration during the flocculation process; finally, after passing through a specific cotton filter layer and a ceramic filter layer, the particles with small nano-particle size are further removed. DETAILED DESCRIPTION

[0038] The present application is further described in detail below with reference to the embodiments.

[0039] The raw materials of the following preparation examples, embodiments and comparative examples are all commercially available, as follows:

[0040] Cationic polyacrylamide for sludge dehydration was purchased from Shanghai Jiejing Chemical Co., Ltd., with a molecular weight of 12 million;

[0041] The CAS number of cationic polyacrylamide is 25085-02-3 and the molecular weight is 167.14;

[0042] The CAS number of ferroferric oxide magnetic nanoparticles is 1317-61-9;

[0043] The CAS number of nano-silicon dioxide is 60676-86-0;

[0044] The length of long-staple cotton is 1-2mm and the fineness is 7000-8000 m / g.

[0045] The ceramic filter membrane was purchased from Zibo Yuding New Material Technology Co., Ltd. with a pore size of 0.1 μm.

[0046] Preparation Example 1

[0047] A method for preparing artificial grinding wastewater is as follows:

[0048] Take 1 liter of ultrapure water, add 80g of nano-silicon dioxide (wherein the particle size of the nano-silicon dioxide is 1-500nm), 4.0g of sodium acetate, and 3.0g of sodium bicarbonate into the ultrapure water, and stir at a speed of 50r / min for 10 minutes to obtain artificial grinding wastewater.

[0049] Example 1

[0050] A method for pretreating grinding wastewater comprises the following steps:

[0051] S1, take 1L of grinding wastewater, and adjust the pH of the grinding wastewater to 7 with 0.1mol / L sodium hydroxide;

[0052] S2, add 0.4g ferrous sulfate and 0.1g ferric chloride to the grinding wastewater, stir for 10 minutes, filter, and take the filtrate, wherein the filter layer used in the filtration process is prepared by mixing ceramic powder, activated carbon and chitosan in a weight ratio of 5:2:3, and its thickness is 10cm, the average particle size of the ceramic powder is between 20-30 microns, and the average particle size of the activated carbon is between 10-20 microns; S3, add 69ml water to the filtrate to make the volume of the filtrate to 1L, and then add 1g ferroferric oxide magnetic nanoparticles and 30g adsorbent, the adsorbent is obtained by mixing activated carbon, diatomaceous earth and magnesium oxide in a weight ratio of 5:3:0.5, the average particle size of the diatomaceous earth is between 15-30 microns, and the average particle size of the activated carbon is between 10-20 microns, stir at a speed of 200r / min for 10 minutes, settle for 30 minutes, and take 500ml of the upper solution;

[0053] S4, add 0.083g aluminum chloride, 0.164g aluminum sulfate, and 0.5g cationic polyacrylamide for sludge dehydration to the upper solution, stir at a speed of 50r / min for 20 minutes, and settle for 30 minutes to obtain the pretreated grinding wastewater;

[0054] S5, passing the filtrate through a cotton filter layer and a ceramic nanofiltration membrane layer in sequence, wherein the cotton filter layer is prepared by mixing long-staple cotton, diatomaceous earth and silicate in a weight ratio of 5:4:3 and has a thickness of 3 cm, and the ceramic nanofiltration membrane layer has a thickness of 0.3 cm, thereby obtaining pretreated grinding wastewater.

[0055] In this embodiment, the grinding wastewater is prepared in Preparation Example 1.

[0056] Example 2

[0057] A method for pretreating grinding wastewater comprises the following steps:

[0058] S1, take 1L of grinding wastewater and adjust the pH of the grinding wastewater to 7 with 0.1mol / L sodium hydroxide;

[0059] S2, adding 0.5g of ferrous sulfate and 0.1g of ferric chloride to the grinding wastewater, stirring for 10 minutes, filtering, and taking the filtrate, wherein the filter layer used in the filtering process is prepared by mixing ceramic powder, activated carbon and chitosan in a weight ratio of 5.5:2.5:3, and its thickness is 10cm, the average particle size of the ceramic powder is between 20-30 microns, and the average particle size of the activated carbon is between 10-20 microns;

[0060] S3, add 71 ml of water to the filtrate to make the volume of the filtrate to 1 L, then add 2 g of ferroferric oxide magnetic nanoparticles and 40 g of adsorbent, the adsorbent is obtained by mixing activated carbon, diatomaceous earth and magnesium oxide in a weight ratio of 6.5:3.5:0.5, the average particle size of diatomaceous earth is between 15-30 microns, and the average particle size of activated carbon is between 10-20 microns, stir at a speed of 300 r / min for 15 minutes, settle for 30 minutes, and take 500 mL of the upper solution;

[0061] S4, add 0.16g aluminum chloride, 0.24g aluminum sulfate, and 0.75g cationic polyacrylamide for sludge dehydration to the upper solution, stir at a speed of 100r / min for 30 minutes, and settle for 30 minutes to obtain the pretreated grinding wastewater;

[0062] S5, passing the filtrate through a cotton filter layer and a ceramic nanofiltration membrane layer in sequence, wherein the cotton filter layer is prepared by mixing long-staple cotton, diatomaceous earth and silicate in a weight ratio of 6.5:5:3 and has a thickness of 3 cm, and the ceramic nanofiltration membrane layer has a thickness of 0.3 cm, thereby obtaining pretreated grinding wastewater.

[0063] In this embodiment, the grinding wastewater is prepared in Preparation Example 1.

[0064] Example 3

[0065] A method for pretreating grinding wastewater comprises the following steps:

[0066] S1, take 1L of grinding wastewater and adjust the pH of the grinding wastewater to 7 with 0.1mol / L sodium hydroxide;

[0067] S2, add 0.45g ferrous sulfate and 0.1g ferric chloride to the grinding wastewater, stir for 10 minutes, filter, and take the filtrate, wherein the filter layer used in the filtration process is prepared by mixing ceramic powder, activated carbon and chitosan in a weight ratio of 6:3:3, and its thickness is 10cm, the average particle size of the ceramic powder is between 20-30 microns, and the average particle size of the activated carbon is between 10-20 microns; S3, add 74ml of water to the filtrate to make the volume of the filtrate to 1L, then add 1.5g of ferroferric oxide magnetic nanoparticles and 50g of adsorbent, the adsorbent is obtained by mixing activated carbon, diatomaceous earth and magnesium oxide in a weight ratio of 8:4:0.5, the average particle size of the diatomaceous earth is between 15-30 microns, and the average particle size of the activated carbon is between 10-20 microns, stir at a speed of 250r / min for 12.5 minutes, settle for 30 minutes, and take 500mL of the upper solution;

[0068] S4, add 0.125g aluminum chloride, 0.375g aluminum sulfate, and 1g cationic polyacrylamide for sludge dehydration to the upper solution, stir at a speed of 75r / min for 25 minutes, and settle for 30 minutes to obtain the pretreated grinding wastewater;

[0069] S5, passing the filtrate through a cotton filter layer and a ceramic nanofiltration membrane layer in sequence, wherein the cotton filter layer is prepared by mixing long-staple cotton, diatomaceous earth and silicate in a weight ratio of 8:7:3 and has a thickness of 3 cm, and the ceramic nanofiltration membrane layer has a thickness of 0.3 cm, thereby obtaining pretreated grinding wastewater.

[0070] In this embodiment, the grinding wastewater is prepared in Preparation Example 1.

[0071] Example 4

[0072] A method for pretreating grinding wastewater, which differs from Example 3 in that an equal amount of alum is used to replace aluminum chloride.

[0073] Example 5

[0074] A method for pretreating grinding wastewater, which differs from Example 3 in that an equal amount of alum is used to replace aluminum sulfate.

[0075] Example 6

[0076] A method for pretreating grinding wastewater, which differs from Example 3 in that in step S2, the weight ratio of ceramic powder, activated carbon and chitosan is 3:2:3.

[0077] Example 7

[0078] A method for pretreating grinding wastewater, which differs from Example 3 in that in step S3, the weight ratio of activated carbon, diatomaceous earth and magnesium oxide is 3:3:0.5.

[0079] Example 8

[0080] A method for pretreating grinding wastewater, which differs from Example 3 in that the demulsifier consists of ferrous sulfate and ferric chloride in a weight ratio of 3:1.

[0081] Example 9

[0082] A method for pretreating grinding wastewater, which differs from Example 3 in that in step S5, the ratio of the thickness of the cotton filter layer to the thickness of the ceramic nanofiltration membrane layer is 25:3.

[0083] Comparative Example 1

[0084] A method for pretreating grinding wastewater, which differs from Example 3 in that step S2 is omitted.

[0085] Comparative Example 2

[0086] A method for pretreating grinding wastewater is different from Example 3 in that the filter layer used in step S2 is a common nano filter layer, the common nano filter layer is a polytetrafluoroethylene membrane, and the filtration accuracy is 0.1 μm.

[0087] Comparative Example 3

[0088] A method for pretreating grinding wastewater, which differs from Example 3 in that talcum powder is used instead of ceramic powder in step S2.

[0089] Comparative Example 4

[0090] A method for pretreating grinding wastewater, which differs from Example 3 in that talcum powder is used instead of activated carbon in step S2.

[0091] Comparative Example 5

[0092] A method for pretreating grinding wastewater, which differs from Example 3 in that chitosan is replaced by chitosan in step S2.

[0093] Comparative Example 6

[0094] A method for pretreating grinding wastewater, which differs from Example 3 in that no demulsifier is added in step S2.

[0095] Comparative Example 7

[0096] A method for pretreating grinding wastewater, which differs from Example 3 in that step S3 is omitted.

[0097] Comparative Example 8

[0098] A method for pretreating grinding wastewater, which differs from Example 3 in that ferrosoferric oxide magnetic nanoparticles are not added in step S3.

[0099] Comparative Example 9 is a method for pretreating grinding wastewater, which differs from Example 3 in that no adsorbent is added in step S3.

[0100] Comparative Example 10

[0101] A method for pretreating grinding wastewater, which differs from Example 3 in that talcum powder is used instead of activated carbon in step S3.

[0102] Comparative Example 11

[0103] A method for pretreating grinding wastewater, which differs from Example 3 in that perlite is used instead of diatomaceous earth in step S3.

[0104] Comparative Example 12

[0105] A method for pretreating grinding wastewater, which differs from Example 3 in that calcium citrate is used instead of magnesium oxide in step S3.

[0106] Comparative Example 13

[0107] A method for pretreating grinding wastewater, which differs from Example 3 in that step S4 is omitted.

[0108] Comparative Example 14

[0109] A method for pretreating grinding wastewater, which differs from Example 3 in that no aluminum salt flocculant is added.

[0110] Comparative Example 15

[0111] A method for pretreating grinding wastewater, which differs from Example 3 in that cationic polyacrylamide for sludge dehydration is not added.

[0112] Comparative Example 16

[0113] A method for pretreating grinding wastewater, which differs from Example 3 in that step S5 is omitted.

[0114] Comparative Example 17

[0115] A method for pretreating grinding wastewater, which differs from Example 3 in that in step S5, only the cotton filter layer is passed.

[0116] Comparative Example 18

[0117] A method for pretreating grinding wastewater, which differs from Example 3 in that in step S5, only the grinding wastewater is filtered through a ceramic nanofiltration membrane layer.

[0118] Comparative Example 19

[0119] A method for pretreating grinding wastewater, which differs from Example 3 in that fine-staple cotton is used instead of long-staple cotton in step S5.

[0120] The length of long-staple cotton is 1-2mm and the fineness is 4500-6000 m / g.

[0121] Comparative Example 20

[0122] A method for pretreating grinding wastewater, which differs from Example 3 in that perlite is used instead of diatomaceous earth in step S5.

[0123] Comparative Example 21

[0124] A method for pretreating grinding wastewater, which differs from Example 3 in that mica is used instead of silicate in step S5.

[0125] Experiment 1 Turbidity detection

[0126] According to HJ1075-2019 "Determination of Turbidity of Water Quality", the turbidity of the grinding wastewater after pretreatment in the above embodiments and comparative examples was tested, and each group was measured three times to take the average value.

[0127] Experiment 2: Detection of suspended solids

[0128] According to GB 11901-1989 "Standard for the Gravimetric Determination of Suspended Solids in Water Quality", the suspended solid content in the grinding wastewater after pretreatment in the above-mentioned embodiments and comparative examples was tested, and each group was tested three times to obtain the average value.

[0129] Experiment 3 Flocculation sedimentation time

[0130] According to the pretreatment method of the above embodiment and comparative example, the time (s) for the floccules to completely settle in step S4 was observed and recorded, and the average value was taken for 3 measurements for each group. The experimental data are shown in Table 1:

[0131] Table 1 Experimental data of Examples 1-9 and Comparative Examples 1-21

[0132]

[0133]

[0134] According to the data comparison of Example 3 and Comparative Examples 1-6 in Table 1, it can be obtained that the turbidity values ​​and suspended solid content values ​​in Comparative Examples 1-6 are significantly higher than those in Example 3; in the flocculation sedimentation time test, the speed of Comparative Examples 1-6 is significantly lower than that of Example 3, indicating that the treatment of step S2 has a high removal efficiency for wastewater containing nano-scale solids, can effectively reduce the suspended matter concentration and turbidity in the wastewater, and accelerate the flocculation of suspended solids in the wastewater.

[0135] According to the data comparison between Example 3 and Comparative Examples 7-12 in Table 1, the turbidity values ​​and suspended solid content values ​​in Comparative Examples 7-12 are significantly higher than those in Example 3; in the flocculation sedimentation time test, the speed of Comparative Examples 7-12 is significantly lower than that of Example 3, indicating that the treatment of step S3 has a high removal efficiency for wastewater containing nano-scale solids, can effectively reduce the suspended matter concentration and turbidity in the wastewater, and accelerate the flocculation of suspended solids in the wastewater.

[0136] According to the data comparison of Example 3 and Comparative Examples 13-15 in Table 1, it can be obtained that the turbidity values ​​and suspended solid content values ​​in Comparative Examples 13-15 are significantly higher than those in Example 3; in the flocculation sedimentation time test, the speed of Comparative Examples 13-15 is significantly lower than that of Example 3, indicating that the treatment of step S4 has a high removal efficiency for wastewater containing nano-scale solids, can effectively reduce the suspended matter concentration and turbidity in the wastewater, and accelerate the flocculation of suspended solids in the wastewater.

[0137] According to the data comparison between Example 3 and Comparative Examples 16-21 in Table 1, the turbidity values ​​and suspended solid content values ​​in Comparative Examples 16-21 are significantly higher than those in Example 3, indicating that the removal efficiency of wastewater containing nano-scale solids is high through the treatment of step S5, and the suspended solid concentration and turbidity in the wastewater can be effectively reduced.

[0138] According to the data comparison of Example 3 and Examples 4-5 and 8 in Table 1, it can be obtained that the turbidity values ​​and the solid suspended matter content values ​​in Examples 4-5 and 8 are significantly higher than those in Example 3; in the flocculation sedimentation time test, the speeds of Examples 4-5 and 8 are significantly lower than those of Example 3, indicating that preparing the adsorbent with a specific ratio of activated carbon, diatomaceous earth and magnesium oxide is beneficial to further enhance the polymerization efficiency of ferroferric oxide magnetic nanoparticles and suspended matter in the grinding wastewater, further improve the sedimentation performance, and reduce the suspended matter concentration and turbidity in the wastewater.

[0139] According to the data comparison between Example 3 and Example 6-7 in Table 1, it can be obtained that the turbidity value and the solid suspended matter content value in Example 6-7 are significantly higher than those in Example 3; in the flocculation sedimentation time test, the speed of Example 6-7 is significantly lower than that of Example 3, indicating that using a specific proportion of ceramic powder, activated carbon and chitosan as the filter layer is beneficial to further enhance the polymerization efficiency of ferroferric oxide magnetic nanoparticles and suspended matter in the grinding wastewater, further improve the sedimentation performance, and reduce the suspended matter concentration and turbidity in the wastewater.

[0140] According to the data comparison between Example 3 and Example 9 in Table 1, the turbidity value and the solid suspended matter content value in Example 9 are significantly higher than those in Example 3, indicating that optimizing the thickness of the cotton filter layer and the thickness ratio of the ceramic nanofiltration membrane layer can reduce the suspended matter concentration and turbidity in the wastewater.

[0141] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.

Claims

1. A method for pretreating grinding wastewater, characterized in that: The following steps are involved: S1, take the grinding wastewater and adjust the pH to 7 with sodium hydroxide or sulfuric acid; S2, adding a demulsifier to the grinding wastewater, stirring, filtering, and taking a filtrate, wherein the filter layer used in the filtering process is prepared by mixing ceramic powder, activated carbon and chitosan; S3, adding ferroferric oxide magnetic nanoparticles and an adsorbent to the filtrate, stirring, settling, and taking an upper layer of the solution, wherein the adsorbent is a mixture of activated carbon, diatomaceous earth, and magnesium oxide; S4, adding aluminum salt flocculant and cationic polyacrylamide for sludge dehydration to the upper solution, stirring, settling, and obtaining a filtrate; S5, passing the filtrate through a cotton filter layer and a ceramic nanofiltration membrane layer in sequence, wherein the cotton filter layer is prepared by mixing long-staple cotton, diatomaceous earth and silicate, thereby obtaining pretreated grinding wastewater; In step S2, the weight ratio of the ceramic powder, the activated carbon and the chitosan is (5-6): (2-3): 3; In step S3, the weight ratio of the activated carbon, the diatomaceous earth and the magnesium oxide is (5-8): (3-4): 0.5; The mass concentration of the ferroferric oxide magnetic nanoparticles in the filtrate is 1-2 g / L and the mass concentration of the adsorbent in the filtrate is 30-50 g / L; The mass concentrations of the aluminum salt flocculant and the cationic polyacrylamide for sludge dehydration in the upper solution are 0.5-1 g / L and 1-2 g / L respectively; The aluminum salt flocculant is composed of aluminum chloride and aluminum sulfate in a weight ratio of 1: (2-3); In step S5, the ratio of the thickness of the cotton filter layer to the thickness of the ceramic nanofiltration membrane layer is (30-50): 3; The demulsifier is composed of ferrous sulfate and ferric chloride in a weight ratio of (4-5):

1.

2. A method for pretreating grinding wastewater according to claim 1, characterized in that: The stirring speed of S3 is 200-300 r / min, and the stirring time is 10-15 minutes.

3. A method for pretreating grinding wastewater according to claim 1, characterized in that: The stirring speed of S4 is 100-150 r / min, and the stirring time is 20-30 minutes.

Citation Information

Patent Citations

  • Comprehensive physical and chemical treatment device and method of organic silicon wastewater

    CN102976537A

  • Semiconductor grinding wastewater treatment method

    CN110316871A

  • Nanometer rapid settling agent for accelerating sludge settling as well as preparation method and application of nanometer rapid settling agent

    CN116177707A